2021
DOI: 10.31616/asj.2020.0008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Counseling and Socioeconomic Factors on Initiation of Rehabilitation Program in Spinal Cord Injury Patients Presenting to a Tertiary Spine Unit in India

Abstract: This study aimed to investigate the impact of education, financial income, occupation, and patient counseling on the timing of enrolment in a spinal cord injury (SCI) rehabilitation program. Overview of Literature: A rehabilitation program following SCI is essential to improve functional outcomes. Socioeconomic factors can affect the timing of enrolment to a rehabilitation program. Literature on the effects of socioeconomic factors among patients with SCI in the Indian scenario is limited. Methods: A prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Several experimental studies have demonstrated that critical processes occur after neuronal damage ( Carlson and Gorden, 2002 ; Kim et al, 2021a ). In cases of traumatic neural damage, secondary injury of neural structures within several minutes of primary injury causes hemorrhage, swelling, ischemia, disrupts feeding vessels, and damages neural tissues ( Aiyer et al, 2021 ), and pro-inflammatory cytokines and chemokines, such as interleukin-1 and 6 (IL-1 and -6) and tumor necrosis factor-alpha (TNF-α), play significant roles in the progression and aggravation of neural structure damage in most processes associated with neural injury ( Qian et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies have demonstrated that critical processes occur after neuronal damage ( Carlson and Gorden, 2002 ; Kim et al, 2021a ). In cases of traumatic neural damage, secondary injury of neural structures within several minutes of primary injury causes hemorrhage, swelling, ischemia, disrupts feeding vessels, and damages neural tissues ( Aiyer et al, 2021 ), and pro-inflammatory cytokines and chemokines, such as interleukin-1 and 6 (IL-1 and -6) and tumor necrosis factor-alpha (TNF-α), play significant roles in the progression and aggravation of neural structure damage in most processes associated with neural injury ( Qian et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%